Effect of Mercury Exposure on the Non Enzymatic Defense System in Workers - Muhsen, J.H; Ahmood, A.M; AL-Taic, W.F; ALÂ Zhaidi, K.A (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The role of free radical generation and lipid peroxidation in most diseases as a scientific explanation for development and destractivc process in biological tissues is confirmed.  In this study, an attempt to shed   li ght  on   the  possible  rel ation  between  some  biochemical parameters as a marker lor antioxidant in sera of (40)workers in  the ticld of mercury was investigated. The workers were divided into twogt-oups according to the_1>_eri odof occupati.On.Group A                        Occupation period